(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Electrical stimulations (ES) of brain structures as well as retinal stimulations have an anti-inflammatory effect and such ES can be used as a method of complex treatment for diabetic retinopathy. The aim of the present paper was to study the activity of glutathione reductase (GR) and of malondialdehyde (MDA) in the retina of the eye, to monitor body mass of rats with streptozotocin (STZ) – induced diabetes as well as to compare changes in these indices in conditions of paleocerebellar electrical stimulations. Material and Methods. Wistar rats were performed ES of paleocerebellar cortex (V-VII lobules) (80-120 mcA, 100 Hz) during four weeks, starting on the 15th day from STZ (55.0 mg/kg, i.p.) administration. At 1.5 months from the moment of the STZ injection, the GR activity and the MDA level were determined in the homogenized retinal tissue and results were expressed as NADPH/min/mg (nM) and nM/mg of protein, respectively. Results. Body weight of the rats with diabetes was increased by 10.7% at the moment of final examination as compared with the baseline indices. In control group of the rats, such increase was 36.2% (P<0.05). That index in diabetes groups treated with ES daily and three times per day was equal to 29.3% and 27.0% (P<0.05), respectively. In the group of the rats which were treated with ES three time per day, the activity of GR in retina increased by 37.0% (P<0.05), аs well as the level of MDA dropped down by 44.5% (P<0.05) pertained to analogous indices in the rats with diabetes. Conclusions: ES of paleocerebellar cortex in the rats with STZ diabetes prevented body weight loss as well as decreasing of GR activity and increasing MDA level in the retinal tissue.